ANALISIS FUNGSI BIAYA STOCHASTIC FRONTIER USAHA PETERNAKAN AYAM PEDAGING PADA PETERNAK YANG MENGGUNAKAN OPEN HOUSE SYSTEM: STOCHASTIC FRONTIER COST FUNCTION ANALYSIS OF BROILER BUSINESS FOR OPEN-HOUSE SYSTEM FARMERS - Stepanus Pakage; Budi Hartono; Zaenal Fanani; Bambang Ali Nugroho; Deny A. Iyai (Jurnal Ilmu Peternakan dan Veteriner Tropis (Journal of Tropical Animal and Veterinary Science), 2019)
This study aims to analyze factors that influence the cost function of broiler farms using open house system. The results indicates that all factors included in the model, simultaneously, affect the production costs. Partially, input such as dayold chick (DOC) costs, feed costs, electricity costs, production positively affect the system. Labor costs on the other hand, have a negative effect on the system. The cost of drugs and fuel has no effect on broiler production costs using the open house system.